Metabolomics and proteomics analyses revealed mechanistic insights on the antimicrobial activity of epigallocatechin gallate against Streptococcus suis - Gao, Ting; Ye, Fei; Tan, Yiqing; Peng, Mingzheng; Yuan, Fangyan; Liu, Zewen; Zhou, Danna; Yang, Keli; Liu, Wei; Guo, Rui; Zhang, Tengfei; Zheng, Lin; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus suis (S. suis) is a highly virulent zoonotic pathogen and causes severe economic losses to the swine industry worldwide. Public health security is also threatened by the rapidly growing antimicrobial resistance in S. suis. Therefore, there is an urgent need to develop new and safe antibacterial alternatives against S. suis. The green tea polyphenol epigallocatechin gallate (EGCG) with a number of potential health benefits is known for its antibacterial effect; however, the mechanism of its bactericidal action remains unclear. In the present, EGCG at minimal inhibitory concentration (MIC) showed significant inhibitory effects on S. suis growth, hemolytic activity, and biofilm formation, and caused damage to S. suis cells in vitro. EGCG also reduced S. suis pathogenicity in Galleria mellonella larvae in vivo. Metabolomics and proteomics analyses were performed to investigate the underlying mechanism of antibacterial activity of EGCG at MIC. Many differentially expressed proteins involved in DNA replication, synthesis of cell wall, and cell membrane, and virulence were down-regulated after the treatment of S. suis with EGCG. EGCG not only significantly reduced the hemolytic activity of S. suis but also down-regulated the expression of suilysin (Sly). The top three shared KEGG pathways between metabolomics and proteomics analysis were ABC transporters, glycolysis/gluconeogenesis, and aminoacyl-tRNA biosynthesis. Taken together, these data suggest that EGCG could be a potential phytochemical compound for treating S. suis infection.